Composite carbon nanofiber catalyst as well as preparation method and application thereof
By preparing composite carbon nanofiber catalysts, using zeolite imidazole ester skeleton material and electrospinning technology, the problem that existing zinc-air battery catalysts cannot effectively catalyze oxygen reduction and oxygen precipitation reactions is solved, and efficient charging and good stability of zinc-air battery are achieved.
Patent Information
- Application Number
- CN202510053605.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-05-02
AI Technical Summary
The existing zinc-air battery catalysts cannot effectively catalyze the oxygen reduction and oxygen precipitation reaction during the battery charging and discharging process, resulting in low charging efficiency.
By preparing a composite carbon nanofiber catalyst, the metal nitrogen carbon material is embedded in the polymer fiber using zeolite imidazole ester framework materials (ZIFs) and electrospinning technology, and secondary carbonization is carried out to form a composite carbon nanofiber catalyst with excellent catalytic activity and stability.
The catalyst exhibits excellent oxygen reduction and oxygen precipitation functions under alkaline conditions, improves the charging efficiency of zinc air batteries, and has good stability and wide application prospects.
Smart Images

Figure CN119920914A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of metal catalysts, in particular to a composite carbon nanofiber catalyst and a preparation method and application thereof. Background Art
[0002] Zinc-air batteries use oxygen in the air as the positive electrode active material, metallic zinc as the negative electrode active material, ammonium chloride or caustic solution as the electrolyte, and generate current through the oxidation of zinc and the reduction reaction of oxygen. Zinc-air batteries have broad development prospects due to their high energy density, green environmental protection, abundant material reserves and low cost. However, there is currently a lack of efficient bifunctional catalysts that can simultaneously catalyze the battery charging and discharging process. In addition, existing catalysts have problems such as low yield, high cost, complex preparation process and poor stability, which cannot effectively accelerate the speed of oxygen reduction (ORR) and oxygen evolution (OER) reactions, thereby affecting the charging efficiency of zinc-air batteries. Therefore, it is particularly important to find a suitable efficient bifunctional catalyst. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing a composite carbon nanofiber catalyst: first, a zeolite imidazolate framework material (ZIFs) is prepared, and metal nitrogen carbon is obtained by the first high-temperature carbonization of the ZIFs powder, and then the metal nitrogen carbon sample is uniformly and stably embedded in the polymer fiber by using the electrospinning technology, and then by secondary carbonization, the graphitization degree of the material is further improved, the conductive property of the material is enhanced, and finally a composite carbon nanofiber catalyst (MN-CNF) is successfully prepared. The catalyst has excellent oxygen reduction (ORR) and oxygen evolution (OER) functions under alkaline conditions. The composite carbon nanofiber material prepared by the present invention using secondary carbonization has good bifunctional catalytic activity and stability, and has broad application prospects.
[0004] The purpose of the present invention is achieved through the following solutions: A composite carbon nanofiber catalyst, the catalyst mainly uses a graphene porous structure formed by carbonization of a fiber polymer as a shell, and a zeolite imidazolate skeleton-derived metal nitrogen-carbon material is coated inside it; the molecular weight of the fiber polymer is 50,000-300,000; the diameter of the catalyst is 5-100nm; the metal is one or more of iron, cobalt, nickel, copper, and zinc; the metal content is 0.1-30wt.%, the nitrogen content is 1-10 atomic%, and the carbon content is 50-95wt.%.
[0005] The catalyst is a metal nitrogen composite carbon nanofiber material formed by carbonizing a zeolite imidazolate skeleton material coated with an organic fiber to derive metal nitrogen and carbon.
[0006] A method for preparing a composite carbon nanofiber catalyst comprises the following steps: (1) Preparation of zeolite imidazolate framework (ZIFs): dissolving a metal salt and an organic ligand in an organic solvent, stirring them evenly, washing them by centrifugation with an organic solvent and anhydrous ethanol respectively, and finally drying and grinding them to obtain a powdered solid ZIFs material; (2) Preparation of metal nitrogen and carbon: placing the ZIFs material described in step (1) in a high-temperature tube furnace filled with inert gas for carbonization treatment, taking it out after cooling and grinding it to obtain metal nitrogen and carbon; (3) Preparation of composite nanofibers: adding the metal nitrogen carbon and fiber polymer described in step (2) to a solvent, stirring evenly to obtain a spinning solution, electrospinning the spinning solution to obtain a composite nanofiber membrane, and obtaining composite nanofibers after drying; (4) Preparation of composite carbon nanofiber catalyst: The composite nanofibers described in step (3) are placed in a high-temperature tubular furnace filled with inert gas for secondary carbonization, and then ground after cooling to finally obtain a composite carbon nanofiber catalyst.
[0007] Preferably, the organic ligand is one or more of 2-methylimidazole, terephthalic acid, 2-ethylimidazole, 2-ethyl-4-methylimidazole, the metal salt is one or more of chloride, nitric acid, sulfuric acid, oxalic acid, acetic acid, carbonate of iron, cobalt, nickel, copper, zinc, and the organic solvent is one of methanol solution, dimethylformamide solution, ethanol solution, and triethylamine solution.
[0008] Preferably, in step (1), the molar ratio of the metal salt to the organic ligand is 1:4 to 1:80, and the molar ratio of the organic ligand to the organic solvent is 1:16 to 1:160; the stirring temperature is 5 to 80°C, the stirring time is 2 to 48 hours, the drying method is forced air drying or vacuum drying, the drying temperature is 40 to 200°C, and the drying time is 8 to 72 hours.
[0009] Preferably, in step (2), the carbonization treatment temperature is 650-1200° C., the carbonization treatment time is 1-12 h, the heating rate is 2-15° C. / min, and the gas flow rate of the inert gas is 10-200 ml / min.
[0010] Preferably, in step (3), the fiber polymer is one or more of left-handed polylactic acid (PLLA), right-handed polylactic acid (PDLA), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyacrylic acid (PAA), cellulose acetate (CA), sodium polystyrene sulfonate (PSS), polyvinyl pyrrolidone (PVP), and polystyrene (PS), and the solvent is one of dimethylformamide (DMF), dimethyl sulfoxide (DMSO), N-methyl-2-pyrrolidone (NMP), and deionized water.
[0011] Preferably, in step (3), the stirring time is 6 to 60 hours, the stirring temperature is 5 to 100° C., wherein the mass ratio of metal nitrogen carbon to fiber polymer is 1:10 to 10:1, and the mass ratio of fiber polymer to solvent is 1:18 to 1:50.
[0012] Preferably, in step (3), the electrospinning syringe is added with 1 to 800 mL of the spinning solution, the voltage of the electrospinning needle is 5 to 40 kV, the capacity of the syringe is 5 to 1000 ml, the injection rate is 0.1 to 10 ml / h, the collection speed is 200 to 1000 rpm, the round-trip distance is 60.0 to 180.0 mm, the receiving distance is 5.0 to 40.0 cm, the spinning temperature is 10 to 50 ° C, the relative humidity is 10 to 60 RH%, the drying conditions are vacuum drying or blast drying, the drying temperature is 40 to 100 ° C, and the drying time is 2 to 48 h.
[0013] Preferably, in step (2) and step (4), the inert gas is one of Ar, He, and N2; in step (4), the secondary carbonization temperature is 500-1400°C, the time is 1-12h, and the heating rate of the secondary carbonization is 2-15°C / min; the gas flow rate of the inert gas is 10-150ml / min, and the inert gas is taken out after the temperature in the furnace drops to room temperature.
[0014] The composite carbon nanofiber catalyst is used as an oxygen electrode in a fuel cell where oxygen participates in the reaction.
[0015] The design concept of the present invention is: Zeolite imidazolate framework material (ZIFs) belongs to the branch of metal organic framework material (MOFs). It is formed by the self-assembly connection of metal center and organic ligand, and has the characteristics of large specific surface area and adjustable pore structure. High specific surface area and pore volume can provide more active sites to improve catalytic efficiency, and the highly ordered pore structure of ZIFs also shows efficient catalytic activity. Carbon nanofibers prepared by electrostatic spinning technology have the characteristics of large specific surface area, porous, hollow, multi-channel, stable structure, etc., which are conducive to the rapid transmission and diffusion of ions and molecules, and can significantly improve their performance in energy storage and catalysis. Therefore, the present invention prepares composite carbon nanofibers by electrostatic spinning technology with zeolite imidazolate framework derived carbon material (metal nitrogen carbon) and polymer, which can not only increase the material specific surface area and improve the active site density, but also enhance the stability of the catalyst during the potential cycle, thereby improving its electrochemical performance. Secondary carbonization can further adjust and optimize the microstructure of the material. After secondary carbonization, the graphitized carbon matrix structure can be further consolidated, the number of micropores, specific surface area and material conductivity can be increased, thereby enhancing its catalytic electron transfer efficiency and thus improving its electrochemical performance.
[0016] First, a zeolite imidazolate skeleton material is prepared by combining metal ions with organic ligands, and then a catalytic active site and a basic carbon skeleton structure of a composite carbon catalyst are formed through a carbonization process to improve the catalytic performance and electrical conductivity of the material itself. Subsequently, the metal nitrogen-carbon particles obtained by carbonization are mixed with polymers, etc., and a spinning solution is prepared. A composite nanofiber membrane is prepared by electrospinning technology, so that the metal nitrogen-carbon active sites are stably and orderly distributed in the organic fiber coating. Subsequently, the composite carbon organic fiber membrane is subjected to secondary carbonization in an inert gas atmosphere to obtain a composite carbon nanofiber catalyst CoN-CNF. The secondary carbonization process constructs a highly conductive porous graphene coating layer for the active sites in the composite carbon, which can not only effectively improve the stability of the active sites, but also provide a quick channel for the transmission of electrons and reactants in the catalytic process. Test studies have shown that the CoN-CNF catalyst prepared by the present invention has excellent electrocatalytic activity and stability, improves the rate of the ORR reaction, and reduces the overpotential of the OER reaction. In the long-term cycle charge and discharge process, it shows good stability and has a wide range of application prospects.
[0017] The technical solution of the present invention has the following advantages and beneficial effects: (1) The present invention synthesizes zeolite imidazolate framework material particles by combining metal ions with organic ligands, using relatively environmentally friendly raw materials, a simple preparation process and a short preparation time. The precursor has the advantages of a highly adjustable pore structure and a large surface area.
[0018] (2) The present invention preliminarily forms composite metal nitrogen-carbon particles having a certain pore structure and electrocatalytic activity through a primary carbonization.
[0019] (3) The present invention utilizes electrospinning technology to embed metal nitrogen and carbon with catalytic activity into polymer fibers, thereby optimizing the spatial distribution of active sites and exposing the catalytic center through the porous structure of the fiber.
[0020] (4) The present invention utilizes a secondary carbonization method, and the carbonization of the fibers forms a graphite closed-loop structure, which provides an electron transfer channel and further improves the conductivity, electrochemical stability, and thermal stability of the material. At the same time, after the secondary carbonization, the microporous structure is optimized, and the density and exposure of the active sites are significantly improved, showing better catalytic performance in the ORR reaction. In addition, the secondary carbonization can also secondary regulate the composition and structure of the catalyst, achieving a uniform distribution of multiple components to synergistically enhance the bifunctional catalytic activity of the catalyst.
[0021] (5) The electrospinning technology of the present invention is simple and easy to operate, with low cost, and can well control the size and porosity of the fiber by adjusting parameters such as voltage and solution concentration. It can spin a wide variety of materials, including various synthetic and natural polymers. The fiber has a small diameter, which can reach the nanometer level, a large specific surface area, a high porosity, good fiber uniformity, good stability, good mechanical properties and flexibility, and can achieve multiple functions by designing a special structure.
[0022] (6) The present invention uses cheap raw materials, simple preparation steps, and a short synthesis cycle, which is conducive to the commercial application of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 ORR and LSV polarization curves of CoN-CNF in 0.1 M KOH.
[0024] Figure 2 OER and LSV polarization curves of CoN-CNF in 1 M KOH.
[0025] Figure 3 ORR and LSV polarization curves of CoN-CNF-2 in 0.1 M KOH.
[0026] Figure 4 OER, LSV polarization curve of CoN-CNF-2 in 1 M KOH.
[0027] Figure 5 ORR and LSV polarization curves of CoN-CNF-3 in 0.1 M KOH.
[0028] Figure 6 OER, LSV polarization curve of CoN-CNF-3 in 1 M KOH. DETAILED DESCRIPTION Example
[0029] A method for preparing a composite carbon nanofiber catalyst comprises the following steps: 1. First, 3.3 g of 2-methylimidazole (2-MIM) was dissolved in dimethylformamide (DMF) and ultrasonically mixed for 10 min to form a uniform solution. Co(NO3)2·6H2O was weighed and added to the solution. The molar ratio of cobalt nitrate hexahydrate to 2-methylimidazole was 1:8, and the molar ratio of 2-methylimidazole to dimethylformamide was 1:16. At 25°C, the mixture was stirred for 2 h until the solution was completely mixed. Then, the mixture was centrifuged and washed three times with DMF and anhydrous ethanol respectively. Finally, the obtained solid sample was placed in a vacuum dryer at a drying temperature of 80°C and a drying time of 12 h. After being taken out, it was ground to obtain a powdered ZIFs material.
[0030] 2. The ZIFs material was placed in a high-temperature tube furnace filled with N2 gas for carbonization treatment, wherein the specific parameters of carbonization were carbonization temperature of 800°C, time of 2h, heating rate of 5°C / min, and inert gas flow rate of 80ml / min. The obtained black powder was ground to obtain metal nitrogen-carbon particles.
[0031] 3. Add 0.5 g of ground metal nitrogen carbon particles and polyacrylonitrile (PAN) into dimethylformamide solution, wherein the mass ratio of metal nitrogen carbon to polyacrylonitrile is 1:2, and the mass ratio of polyacrylonitrile to dimethylformamide solution is 1:18. The mixed solution is magnetically stirred for 24 hours at 20°C to obtain a uniformly mixed spinning solution.
[0032] 4. Take 5 ml of the spinning solution and transfer it to a syringe for electrostatic spinning, collect the composite nanofiber membrane, and place the composite nanofiber membrane in a vacuum drying oven at 80°C for 12 hours to obtain composite nanofibers. The specific parameters of electrospinning are as follows: the voltage of the needle is 15 kV, the capacity of the syringe is 10 ml, the injection rate is 1.0 ml / h, the collection speed is 450 rpm, the round-trip distance is 120.0 mm, the receiving distance is 20 cm, the spinning temperature is 25°C, and the relative humidity is 30 RH%.
[0033] 5. The obtained composite nanofibers were subjected to a second carbonization treatment under an inert gas N2, wherein the specific carbonization parameters were: carbonization temperature 900°C, time 2h, heating rate 5°C / min, and inert gas flow rate 80mL / min.
[0034] 6. After carbonization, the obtained carbon nanomaterial is taken out and ground to finally obtain a composite carbon nanofiber catalyst (CoN-CNF). Example
[0035] A method for preparing a composite carbon nanofiber catalyst comprises the following steps: 1. First, 3.3 g of 2-methylimidazole (2-MIM) was dissolved in dimethylformamide (DMF) and ultrasonically mixed for 10 min to form a uniform solution. Co(NO3)2·6H2O was weighed and added to the solution. The molar ratio of cobalt nitrate hexahydrate to dimethylimidazole was 1:8, and the molar ratio of dimethylimidazole to dimethylformamide was 1:16. At 25°C, the mixture was stirred for 2 h until the solution was completely mixed. Then, the mixture was centrifuged and washed three times with DMF and anhydrous ethanol respectively. Finally, the obtained solid sample was placed in a vacuum dryer at a drying temperature of 80°C and a drying time of 12 h. After being taken out, it was ground to obtain a powdered ZIFs material.
[0036] 2. The ZIFs material was placed in a high-temperature tube furnace filled with N2 gas for carbonization treatment, wherein the specific parameters of carbonization were carbonization temperature of 800°C, time of 2h, heating rate of 5°C / min, and inert gas flow rate of 80mL / min. The obtained black powder was ground to obtain metal nitrogen-carbon particles.
[0037] 3. Add the ground metal nitrogen carbon particles and polyacrylonitrile (PAN) into the dimethylformamide solution, wherein the mass ratio of metal nitrogen carbon particles to polyacrylonitrile is 1:2, and the mass ratio of polyacrylonitrile to dimethylformamide solution is 1:18. The mixed solution is magnetically stirred for 24 hours at 20°C to obtain a uniformly mixed spinning solution.
[0038] 4. Take 5 ml of the spinning solution and transfer it to a syringe for electrostatic spinning, collect the composite nanofiber membrane, and place the composite nanofiber membrane in a vacuum drying oven at 80°C for 12 hours to obtain composite nanofibers. The specific parameters of electrospinning are as follows: the voltage of the needle is 15 kV, the capacity of the syringe is 10 ml, the injection rate is 1 ml / h, the collection speed is 450 rpm, the round-trip distance is 120.0 mm, the receiving distance is 20 cm, the spinning temperature is 25°C, and the relative humidity is 30 RH%.
[0039] 5. The obtained composite nanofibers were subjected to a second carbonization treatment under an inert gas N2, wherein the specific carbonization parameters were: carbonization temperature 500°C, time 2h, heating rate 5°C / min, and inert gas flow rate 80mL / min.
[0040] 6. After the carbonization is completed, the obtained carbon nanomaterial is taken out and ground to finally obtain a composite carbon nanofiber catalyst (CoN-CNF-2). Example
[0041] A method for preparing a composite carbon nanofiber catalyst comprises the following steps: 1. First, 3.3 g of 2-methylimidazole (2-MIM) was dissolved in dimethylformamide (DMF) and ultrasonically mixed for 10 min to form a uniform solution. Co(NO3)2·6H2O was weighed and added to the solution. The molar ratio of cobalt nitrate hexahydrate to dimethylimidazole was 1:8, and the molar ratio of dimethylimidazole to dimethylformamide was 1:16. At 25°C, the mixture was stirred for 2 h until the solution was completely mixed. Then, the mixture was centrifuged and washed three times with DMF and anhydrous ethanol respectively. Finally, the obtained solid sample was placed in a vacuum dryer at a drying temperature of 80°C and a drying time of 12 h. After being taken out, it was ground to obtain a powdered ZIFs material.
[0042] 2. The ZIFs material was placed in a high-temperature tube furnace filled with N2 gas for carbonization treatment, wherein the specific parameters of carbonization were carbonization temperature of 800°C, time of 2h, heating rate of 5°C / min, and inert gas flow rate of 80mL / min. The obtained black powder was ground to obtain metal nitrogen-carbon particles.
[0043] 3. Add 0.5 g of ground metal nitrogen carbon particles and polyacrylonitrile (PAN) into the dimethylformamide solution, wherein the mass ratio of metal nitrogen carbon particles to polyacrylonitrile is 1:2, and the mass ratio of polyacrylonitrile to dimethylformamide solution is 1:10. The mixed solution is magnetically stirred for 24 hours at 20°C to obtain a uniformly mixed spinning solution.
[0044] 4. Take 5 ml of the spinning solution and transfer it to a syringe for electrostatic spinning, collect the composite nanofiber membrane, and place the composite nanofiber membrane in a vacuum drying oven at 80°C for 12 hours to obtain composite nanofibers. The specific parameters of electrospinning are as follows: the voltage of the needle is 15 kV, the capacity of the syringe is 10 ml, the injection rate is 1 ml / h, the collection speed is 450 rpm, the round-trip distance is 120.0 mm, the receiving distance is 20 cm, the spinning temperature is 25°C, and the relative humidity is 30 RH%.
[0045] 5. The obtained composite nanofibers were subjected to a second carbonization treatment under an inert gas N2, wherein the specific carbonization parameters were: carbonization temperature 800°C, time 2h, heating rate 5°C / min, and inert gas flow rate 80mL / min.
[0046] 6. After the carbonization is completed, the obtained carbon nanomaterial is taken out and ground to finally obtain a composite carbon nanofiber catalyst (CoN-CNF-3). Example
[0047] A method for preparing a composite carbon nanofiber catalyst comprises the following steps: 1. First, 3.3 g of 2-methylimidazole (2-MIM) was dissolved in methanol and ultrasonically mixed for 10 minutes to form a uniform solution. Then, ferric chloride hexahydrate was added to the solution, the molar ratio of ferric chloride hexahydrate to dimethylimidazole was 1:16, and the molar ratio of dimethylimidazole to methanol was 1:32. At 25°C, the mixture was stirred for 2 hours until the solution was completely mixed. Then, the mixture was centrifuged and washed three times with DMF and anhydrous ethanol respectively, and finally, the obtained solid sample was placed in a vacuum dryer at a drying temperature of 80°C and a drying time of 12 hours. After being taken out, it was ground to obtain a powdered ZIFs material.
[0048] 2. The ZIFs material was placed in a high-temperature tube furnace filled with He gas for carbonization treatment, wherein the specific parameters of carbonization were carbonization temperature of 650°C, time of 2h, heating rate of 8°C / min, and inert gas flow rate of 80mL / min. The obtained black powder was ground to obtain metal nitrogen-carbon particles.
[0049] 3. Add 0.5 g of ground metal nitrogen carbon particles and polyvinylidene fluoride (PVDF) into dimethylformamide solution, wherein the mass ratio of metal nitrogen carbon particles to polyvinylidene fluoride is 1:1, and the mass ratio of polyvinylidene fluoride to dimethylformamide solution is 1:18. The mixed solution is magnetically stirred for 24 hours at 20°C to obtain a uniformly mixed spinning solution.
[0050] 4. Take 5 ml of the spinning solution and transfer it to a syringe for electrostatic spinning, collect the composite nanofiber membrane, and place the composite nanofiber membrane in a vacuum drying oven at 80°C for 12 hours to obtain composite nanofibers. The specific parameters of electrospinning are as follows: the voltage of the needle is 15 kV, the capacity of the syringe is 10 ml, the injection rate is 1.0 ml / h, the collection speed is 450 rpm, the round-trip distance is 120.0 mm, the receiving distance is 20 cm, the spinning temperature is 25°C, and the relative humidity is 30 RH%.
[0051] 5. The obtained composite nanofibers were subjected to a second carbonization treatment under an inert gas He, wherein the specific carbonization parameters were: carbonization temperature of 1200°C, time of 2h, heating rate of 6°C / min, and inert gas flow rate of 80mL / min.
[0052] 6. After the carbonization is completed, the obtained carbon nanomaterial is taken out and ground to finally obtain a composite carbon nanofiber catalyst (CoN-CNF-4). Example
[0053] A method for preparing a composite carbon nanofiber catalyst comprises the following steps: 1. First, 3.3 g of terephthalic acid (PTA) was dissolved in dimethylformamide (DMF) and ultrasonically mixed for 10 min to form a uniform solution. Zinc nitrate hexahydrate was weighed and added to the solution. The molar ratio of zinc nitrate hexahydrate to terephthalic acid was 1:32, and the molar ratio of terephthalic acid to dimethylformamide was 1:42. At 25 ° C, the mixture was stirred for 2 h until the solution was completely mixed. Then, the mixture was centrifuged and washed three times with DMF and anhydrous ethanol respectively. Finally, the obtained solid sample was placed in a vacuum dryer at a drying temperature of 80 ° C and a drying time of 12 h. After being taken out, it was ground to obtain a powdered ZIFs material.
[0054] 2. The ZIFs material was placed in a high-temperature tube furnace filled with N2 gas for carbonization treatment, wherein the specific parameters of carbonization were carbonization temperature of 700°C, time of 4h, heating rate of 10°C / min, and inert gas flow rate of 80mL / min. The obtained black powder was ground to obtain metal nitrogen-carbon particles.
[0055] 3. Add 0.5 g of ground metal nitrogen carbon particles and right-handed polylactic acid (PDLA) into the dimethylformamide solution, wherein the mass ratio of metal nitrogen carbon particles to right-handed polylactic acid is 1:3, and the mass ratio of right-handed polylactic acid to dimethylformamide solution is 1:20. The mixed solution is magnetically stirred for 24 hours at 20°C to obtain a uniformly mixed spinning solution.
[0056] 4. Take 5 ml of the spinning solution and transfer it to a syringe for electrostatic spinning. Collect the composite nanofiber membrane, place the composite nanofiber membrane in a vacuum drying oven, and vacuum dry it at 80°C for 12 hours to obtain composite nanofibers. The specific parameters of electrostatic spinning are as follows: the voltage of the needle is 20 kV, the capacity of the syringe is 10 ml, the injection rate is 0.6 ml / h, the collection speed is 450 rpm, the round-trip distance is 120.0 mm, the receiving distance is 20 cm, the spinning temperature is 25°C, and the relative humidity is 25 RH%.
[0057] 5. The obtained composite nanofibers were subjected to a second carbonization treatment under an inert gas N2, wherein the specific carbonization parameters were: carbonization temperature 1300°C, time 2h, heating rate 5°C / min, and inert gas flow rate 100mL / min.
[0058] 6. After carbonization, the obtained carbon nanomaterial is taken out and ground to finally obtain a composite carbon nanofiber catalyst (CoN-CNF-5). Example
[0059] A method for preparing a composite carbon nanofiber catalyst comprises the following steps: 1. First, 3.3 g of 2-methylimidazole (2-MIM) was dissolved in dimethylformamide (DMF) and ultrasonically mixed for 10 min to form a uniform solution. Nickel nitrate hexahydrate was weighed and added to the solution. The molar ratio of nickel nitrate hexahydrate to dimethylimidazole was 1:8, and the molar ratio of dimethylimidazole to dimethylformamide was 1:16. At 25 ° C, the mixture was stirred for 2 h until the solution was completely mixed. Then, the mixture was centrifuged and washed three times with DMF and anhydrous ethanol respectively. Finally, the obtained solid sample was placed in a vacuum dryer at a drying temperature of 80 ° C and a drying time of 12 h. After being taken out, it was ground to obtain a powdered ZIFs material.
[0060] 2. The ZIFs material was placed in a high-temperature tubular furnace filled with Ar gas for carbonization treatment, wherein the specific parameters of carbonization were carbonization temperature of 800°C, time of 2h, heating rate of 6°C / min, and inert gas flow rate of 80mL / min. The obtained black powder was ground to obtain metal nitrogen-carbon particles.
[0061] 3. Add 0.5 g of ground metal nitrogen carbon particles and polyacrylic acid (PAA) into the dimethylformamide solution, wherein the mass ratio of metal nitrogen carbon particles to polyacrylic acid (PAA) is 1:1, and the mass ratio of polyacrylic acid to dimethylformamide solution is 1:30. The mixed solution is magnetically stirred for 24 hours at 20°C to obtain a uniformly mixed spinning solution.
[0062] 4. Take 5 ml of the spinning solution and transfer it to a syringe for electrostatic spinning, collect the composite nanofiber membrane, and place the composite nanofiber membrane in a vacuum drying oven at 80°C for 12 hours to obtain composite nanofibers. The specific parameters of electrospinning are as follows: the voltage of the needle is 15 kV, the capacity of the syringe is 10 ml, the injection rate is 0.9 ml / h, the collection speed is 450 rpm, the round-trip distance is 120.0 mm, the receiving distance is 20 cm, the spinning temperature is 25°C, and the relative humidity is 30 RH%.
[0063] 5. The obtained composite nanofibers were subjected to a second carbonization treatment under an inert gas Ar, wherein the specific carbonization parameters were: carbonization temperature 1400°C, time 4h, heating rate 6°C / min, and inert gas flow rate 120mL / min.
[0064] 6. After the carbonization is completed, the obtained carbon nanomaterial is taken out and ground to finally obtain a composite carbon nanofiber catalyst (CoN-CNF-6). Example
[0065] A method for preparing a composite carbon nanofiber catalyst comprises the following steps: 1. First, 3.3 g of 2-ethylimidazole was dissolved in dimethylformamide (DMF) and ultrasonically mixed for 10 min to form a uniform solution. Co(NO3)2·6H2O was weighed and added to the solution. The molar ratio of cobalt nitrate hexahydrate to 2-ethylimidazole was 1:12, and the molar ratio of 2-ethylimidazole to dimethylformamide was 1:22. At 25°C, the mixture was stirred for 2 h until the solution was completely mixed. Then, the mixture was centrifuged and washed three times with DMF and anhydrous ethanol respectively. Finally, the obtained solid sample was placed in a vacuum dryer at a drying temperature of 80°C and a drying time of 12 h. After being taken out, it was ground to obtain a powdered ZIFs material.
[0066] 2. The ZIFs material was placed in a high-temperature tube furnace filled with N2 gas for carbonization treatment, wherein the specific parameters of carbonization were carbonization temperature of 800°C, time of 2h, heating rate of 6°C / min, and inert gas flow rate of 100mL / min. The obtained black powder was ground to obtain metal nitrogen-carbon particles.
[0067] 3. Add 0.5 g of ground metal nitrogen carbon particles and polyacrylonitrile (PAN) to the dimethylformamide solution, wherein the mass ratio of metal nitrogen carbon particles to polyacrylonitrile is 1:2, and the mass ratio of polyacrylonitrile to dimethylformamide solution is 1:32. The mixed solution is magnetically stirred at 20°C for 48 hours to obtain a uniformly mixed spinning solution.
[0068] 4. Take 5 ml of the spinning solution and transfer it to a syringe for electrostatic spinning, collect the composite nanofiber membrane, and place the composite nanofiber membrane in a vacuum drying oven at 80°C for 12 hours to obtain composite nanofibers. The specific parameters of electrospinning are as follows: the voltage of the needle is 15 kV, the capacity of the syringe is 10 ml, the injection rate is 1.0 ml / h, the collection speed is 450 rpm, the round-trip distance is 120.0 mm, the receiving distance is 20 cm, the spinning temperature is 25°C, and the relative humidity is 30 RH%.
[0069] 5. The obtained composite nanofibers were subjected to a second carbonization treatment under an inert gas N2, wherein the specific carbonization parameters were: carbonization temperature 600°C, time 2h, heating rate 6°C / min, and inert gas flow rate 80mL / min.
[0070] 6. After carbonization, the obtained carbon nanomaterial is taken out and ground to finally obtain a composite carbon nanofiber catalyst (CoN-CNF-7). Example
[0071] A method for preparing a composite carbon nanofiber catalyst comprises the following steps: 1. First, 3.3 g of 2-ethyl-4-methylimidazole was dissolved in methanol and ultrasonically mixed for 10 min to form a uniform solution. Co(NO3)2·6H2O was weighed and added to the solution. The molar ratio of cobalt nitrate hexahydrate to 2-ethyl-4-methylimidazole was 1:8, and the molar ratio of 2-ethyl-4-methylimidazole to methanol was 1:16. At 25°C, the mixture was stirred for 2 h until the solution was completely mixed. Then, the mixture was centrifuged and washed three times with DMF and anhydrous ethanol respectively. Finally, the obtained solid sample was placed in a vacuum dryer at a drying temperature of 80°C and a drying time of 12 h. After being taken out, it was ground to obtain a powdered ZIFs material.
[0072] 2. The ZIFs material was placed in a high-temperature tube furnace filled with N2 gas for carbonization treatment, wherein the specific parameters of carbonization were carbonization temperature of 800°C, time of 2h, heating rate of 6°C / min, and inert gas flow rate of 80mL / min. The obtained black powder was ground to obtain metal nitrogen-carbon particles.
[0073] 3. Add 0.5 g of ground metal nitrogen carbon particles and L-polylactic acid (PLLA) into the dimethylformamide solution, wherein the mass ratio of metal nitrogen carbon particles to L-polylactic acid is 1:2, and the mass ratio of L-polylactic acid to dimethylformamide solution is 1:35. The mixed solution is magnetically stirred for 24 hours at 20°C to obtain a uniformly mixed spinning solution.
[0074] 4. Take 6 ml of the above spinning solution and transfer it to the syringe, perform high-voltage electrospinning at an injection speed of 1.0 mL / h, collect the composite nanofiber membrane, and place the spun polymer fiber membrane in a vacuum drying oven at 80°C for 12 hours to obtain composite nanofibers. The specific parameters of electrospinning are as follows: the voltage of the needle is 13 kV, the capacity of the syringe is 10 ml, the injection rate is 1.0 ml / h, the collection speed is 450 rpm, the round-trip distance is 120.0 mm, the receiving distance is 15 cm, the spinning temperature is 25°C, and the relative humidity is 30 RH%.
[0075] 5. The obtained composite nanofibers were subjected to a second carbonization treatment under an inert gas N2, wherein the specific carbonization parameters were: carbonization temperature 700°C, time 2h, heating rate 6°C / min, and inert gas flow rate 80mL / min.
[0076] 6. After the carbonization is completed, the obtained carbon nanomaterial is taken out and ground to finally obtain a composite carbon nanofiber catalyst (CoN-CNF-8). Example
[0077] A method for preparing a composite carbon nanofiber catalyst comprises the following steps: 1. First, 3.3 g of 2-methylimidazole (2-MIM) was dissolved in dimethylformamide (DMF) and ultrasonically mixed for 10 min to form a uniform solution. Co(NO3)2·6H2O was weighed and added to the solution. The molar ratio of cobalt nitrate hexahydrate to dimethylimidazole was 1:8, and the molar ratio of dimethylimidazole to dimethylformamide was 1:16. At 25°C, the mixture was stirred for 2 h until the solution was completely mixed. Then, the mixture was centrifuged and washed three times with DMF and anhydrous ethanol respectively. Finally, the obtained purple solid sample was vacuum dried at 85°C for 10 h, and then ground to obtain a powdered ZIFs material.
[0078] 2. The ZIFs material was placed in a high-temperature tube furnace filled with N2 gas for carbonization treatment, wherein the specific parameters of carbonization were carbonization temperature of 800°C, time of 2h, heating rate of 5°C / min, and inert gas flow rate of 80mL / min. The obtained black powder was ground to obtain metal nitrogen-carbon particles.
[0079] 3. Add the ground metal nitrogen carbon particles and polyvinyl pyrrolidone (PVP) to the dimethylformamide solution, wherein the mass ratio of the metal nitrogen carbon particles to the polyvinyl pyrrolidone is 1:2, and the mass ratio of the polyvinyl pyrrolidone to the dimethylformamide solution is 1:37. The mixed solution is magnetically stirred for 24 hours at 20°C to obtain a uniformly mixed spinning solution.
[0080] 4. Take 5 ml of the spinning solution and transfer it to a syringe for electrostatic spinning, collect the composite nanofiber membrane, and place the composite nanofiber membrane in a vacuum drying oven at 80°C for 12 hours to obtain composite nanofibers. The specific parameters of electrospinning are as follows: the voltage of the needle is 15 kV, the capacity of the syringe is 10 ml, the injection rate is 1.0 ml / h, the collection speed is 450 rpm, the round-trip distance is 120.0 mm, the receiving distance is 20 cm, the spinning temperature is 25°C, and the relative humidity is 30 RH%.
[0081] 5. The obtained composite nanofibers were subjected to a second carbonization treatment under an inert gas N2, wherein the specific carbonization parameters were: carbonization temperature 1000°C, time 2h, heating rate 8°C / min, and inert gas flow rate 80mL / min.
[0082] 6. After the carbonization is completed, the obtained carbon nanomaterial is taken out and ground to finally obtain a composite carbon nanofiber catalyst (CoN-CNF-9). Example
[0083] A method for preparing a composite carbon nanofiber catalyst comprises the following steps: 1. First, 3.3 g of 2-methylimidazole (2-MIM) was dissolved in dimethylformamide (DMF) and ultrasonically mixed for 10 min to form a uniform solution. Co(NO3)2·6H2O was weighed and added to the solution. The molar ratio of cobalt nitrate hexahydrate to dimethylimidazole was 1:25, and the molar ratio of dimethylimidazole to dimethylformamide was 1:44. At 25°C, the mixture was stirred for 2 h until the solution was completely mixed. Then, the mixture was centrifuged and washed three times with DMF and anhydrous ethanol respectively. Finally, the obtained solid sample was placed in a vacuum dryer at a drying temperature of 80°C and a drying time of 12 h. After being taken out, it was ground to obtain a powdered ZIFs material.
[0084] 2. The ZIFs material was placed in a high-temperature tubular furnace filled with Ar gas for carbonization treatment, wherein the specific parameters of carbonization were carbonization temperature of 800°C, time of 2h, heating rate of 6°C / min, and inert gas flow rate of 80mL / min. The obtained black powder was ground to obtain metal nitrogen-carbon particles.
[0085] 3. Add 0.5 g of ground metal nitrogen carbon particles and polyacrylonitrile (PAN) into the dimethylformamide solution, wherein the mass ratio of metal nitrogen carbon particles to polyacrylonitrile is 1:2, and the mass ratio of polyacrylonitrile to dimethylformamide solution is 1:40. The mixed solution is magnetically stirred for 24 hours at 20°C to obtain a uniformly mixed spinning solution.
[0086] 4. Take 5 ml of the spinning solution and transfer it to a syringe for electrostatic spinning, collect the composite nanofiber membrane, and place the composite nanofiber membrane in a vacuum drying oven at 80°C for 12 hours to obtain composite nanofibers. The specific parameters of electrospinning are as follows: the voltage of the needle is 15 kV, the capacity of the syringe is 10 ml, the injection rate is 0.8 ml / h, the collection speed is 450 rpm, the round-trip distance is 120.0 mm, the receiving distance is 20 cm, the spinning temperature is 25°C, and the relative humidity is 30 RH%.
[0087] 5. The obtained composite nanofibers were subjected to a second carbonization treatment under an inert gas Ar, wherein the specific carbonization parameters were: carbonization temperature 1100°C, time 2h, heating rate 6°C / min, and inert gas flow rate 80mL / min.
[0088] 6. After the carbonization is completed, the obtained carbon nanomaterial is taken out and ground to finally obtain a composite carbon nanofiber catalyst (CoN-CNF-10). Example
[0089] A method for preparing a composite carbon nanofiber catalyst comprises the following steps: 1. First, dissolve 3.3g of 2-methylimidazole (2-MIM) in dimethylformamide (DMF) and form a uniform solution after ultrasonic mixing for 10 minutes. Weigh cobalt acetate and add it to the solution. The molar ratio of cobalt acetate to dimethylimidazole is 1:12, and the molar ratio of dimethylimidazole to dimethylformamide is 1:30. Mix and stir for 2 hours at 25°C until the solution is completely mixed. Then centrifuge and wash three times with DMF and anhydrous ethanol respectively. Finally, place the obtained solid sample in a vacuum dryer at a drying temperature of 80°C and a drying time of 12 hours. Grind it after taking it out to obtain a powdered ZIFs material.
[0090] 2. The ZIFs material was placed in a high-temperature tube furnace filled with N2 gas for carbonization treatment, wherein the specific parameters of carbonization were carbonization temperature of 800°C, time of 2h, heating rate of 6°C / min, and inert gas flow rate of 80mL / min. The obtained black powder was ground to obtain metal nitrogen-carbon particles.
[0091] 3. Add 0.5 g of ground metal nitrogen carbon particles and polyacrylonitrile (PAN) into the dimethylformamide solution, wherein the mass ratio of metal nitrogen carbon particles to polyacrylonitrile is 2:1, and the mass ratio of polyacrylonitrile to dimethylformamide solution is 1:45. The mixed solution is magnetically stirred for 32 hours at 20°C to obtain a uniformly mixed spinning solution.
[0092] 4 Take 5 ml of the spinning solution and transfer it to a syringe for electrospinning, collect the composite nanofiber membrane, place the composite nanofiber membrane in a vacuum drying oven, and vacuum dry it at 80°C for 12 hours to obtain composite nanofibers. The specific parameters of electrospinning are as follows: the voltage of the needle is 15 kV, the capacity of the syringe is 10 ml, the injection rate is 0.8 ml / h, the collection speed is 450 rpm, the round-trip distance is 120.0 mm, the receiving distance is 20 cm, the spinning temperature is 25°C, and the relative humidity is 30 RH%.
[0093] 5. The obtained composite nanofibers were subjected to a second carbonization treatment under an inert gas N2, wherein the specific carbonization parameters were: carbonization temperature 1200°C, time 2h, heating rate 6°C / min, and inert gas flow rate 80mL / min.
[0094] 6. After the carbonization is completed, the obtained carbon nanomaterial is taken out and ground to finally obtain a composite carbon nanofiber catalyst (CoN-CNF-11). Example
[0095] A method for preparing a composite carbon nanofiber catalyst comprises the following steps: 1. First, dissolve 3.3g of 2-methylimidazole (2-MIM) in methanol and form a uniform solution after ultrasonic mixing for 10 minutes. Weigh cobalt oxalate and add it to the solution. The molar ratio of cobalt oxalate to dimethylimidazole is 1:10, and the molar ratio of dimethylimidazole to methanol is 1:18. Mix and stir for 2h at 25°C until the solution is completely mixed. Then centrifuge and wash three times with methanol and anhydrous ethanol respectively. Finally, place the obtained solid sample in a vacuum dryer at a drying temperature of 80°C and a drying time of 12h. Grind it after taking it out to obtain a powdered ZIFs material.
[0096] 2. The ZIFs material was placed in a high-temperature tube furnace filled with N2 gas for carbonization treatment, wherein the specific parameters of carbonization were carbonization temperature of 800°C, time of 2h, heating rate of 6°C / min, and inert gas flow rate of 80mL / min. The obtained black powder was ground to obtain metal nitrogen-carbon particles.
[0097] 3. Add 0.5 g of ground metal nitrogen carbon particles and polyvinyl pyrrolidone (PVP) to the dimethylformamide solution, wherein the mass ratio of metal nitrogen carbon particles to polyvinyl pyrrolidone is 2:3, and the mass ratio of polyvinyl pyrrolidone to dimethylformamide solution is 1:50. The mixed solution is magnetically stirred at 30°C for 24 hours to obtain a uniformly mixed spinning solution.
[0098] 4. Take 5 ml of the spinning solution and transfer it to a syringe for electrospinning, collect the composite nanofiber membrane, and place the composite nanofiber membrane in a vacuum drying oven at 80°C for 12 hours to obtain composite nanofibers. The specific parameters of electrospinning are as follows: the voltage of the needle is 15 kV, the capacity of the syringe is 10 ml, the injection rate is 0.8 ml / h, the collection speed is 450 rpm, the round-trip distance is 120.0 mm, the receiving distance is 20 cm, the spinning temperature is 25°C, and the relative humidity is 35 RH%.
[0099] 5. The obtained composite nanofibers were subjected to a second carbonization treatment under an inert gas N2, wherein the specific carbonization parameters were: carbonization temperature 1300°C, time 2h, heating rate 6°C / min, and inert gas flow rate 80mL / min.
[0100] 6. After the carbonization is completed, the obtained carbon nanomaterial is taken out and ground to finally obtain a composite carbon nanofiber catalyst (CoN-CNF-12).
[0101] The results of this embodiment show that the present invention first carbonizes the zeolite imidazolate framework material (ZIFs) to obtain metal nitrogen-carbon particles with catalytic activity, and then uses electrospinning technology to connect the metal nitrogen-carbon particles in series to the polymer, thereby achieving a microscopic composite of the two at the nanoscale to form a nanofiber network structure, and then the composite nanofibers are secondary carbonized. Through the secondary carbonization treatment, the density and exposure of the active sites are increased, and at the same time, the composition and structure of the catalyst are precisely controlled, the stability of the catalyst is further enhanced, the uniform dispersion and synergistic effect of multiple components are achieved, and the electrical conductivity of the material itself is enhanced, which is of great significance for promoting the industrial development of zinc-air batteries.
Claims
1. A composite carbon nanofiber catalyst, characterized in that: The catalyst mainly uses a graphene porous structure formed by carbonization of a fiber polymer as its shell, and a zeolite imidazolate skeleton-derived metal nitrogen-carbon material is coated inside it; the molecular weight of the fiber polymer is 50,000-300,000; the diameter of the catalyst is 5-100 nm; the metal is one or more of iron, cobalt, nickel, copper, and zinc; the content of the metal is 0.01-30 wt.%, the content of the nitrogen is 1-10 atomic%, and the content of the carbon is 50-95 wt.%.
2. A method for preparing the composite carbon nanofiber catalyst according to claim 1, characterized in that: The following steps are involved: (1) Preparation of zeolite imidazolate framework (ZIFs): dissolving a metal salt and an organic ligand in an organic solvent, stirring them evenly, washing them by centrifugation with an organic solvent and anhydrous ethanol respectively, and finally drying and grinding them to obtain a powdered solid ZIFs material; (2) Preparation of metal nitrogen and carbon: placing the ZIFs material described in step (1) in a high-temperature tube furnace filled with inert gas for carbonization treatment, taking it out after cooling and grinding it to obtain the metal nitrogen and carbon material; (3) Preparation of composite nanofibers: adding the metal nitrogen carbon and fiber polymer described in step (2) to a solvent, stirring evenly to obtain a spinning solution, electrospinning the spinning solution to obtain a composite nanofiber membrane, and obtaining composite nanofibers after drying; (4) Preparation of composite carbon nanofiber catalyst: The composite nanofibers described in step (3) are placed in a high-temperature tubular furnace filled with inert gas for secondary carbonization, and then ground after cooling to finally obtain a composite carbon nanofiber catalyst.
3. The method according to claim 2, characterized in that In step (1), the organic ligand is one or more of 2-methylimidazole, terephthalic acid, 2-ethylimidazole, 2-ethyl-4-methylimidazole, the metal salt is one or more of chloride, nitric acid, sulfuric acid, oxalic acid, acetic acid, carbonate of iron, cobalt, nickel, copper, zinc, and the organic solvent is one of methanol solution, dimethylformamide solution, ethanol solution, and triethylamine solution.
4. The method according to claim 2, characterized in that: In step (1), the molar ratio of the metal salt to the organic ligand is 1:2 to 1:80, and the molar ratio of the organic ligand to the organic solvent is 1:16 to 1:160; the stirring temperature is 5 to 80°C, the stirring time is 2 to 48 hours, the drying method is forced air drying or vacuum drying, the drying temperature is 40 to 150°C, and the drying time is 8 to 72 hours.
5. The method according to claim 2, characterized in that: In step (2), the carbonization treatment temperature is 650-1200° C., the carbonization treatment time is 1-12 h, the heating rate is 2-15° C. / min, and the gas flow rate of the inert gas is 10-200 ml / min.
6. The method according to claim 2, characterized in that In step (3), the fiber polymer is one or more of left-handed polylactic acid (PLLA), right-handed polylactic acid (PDLA), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyacrylic acid (PAA), cellulose acetate (CA), sodium polystyrene sulfonate (PSS), polyvinyl pyrrolidone (PVP), and polystyrene (PS), and the solvent is one of dimethylformamide (DMF), dimethyl sulfoxide (DMSO), N-methyl-2-pyrrolidone (NMP), and deionized water.
7. The method according to claim 2, characterized in that In step (3), the stirring time is 6 to 60 hours, the stirring temperature is 5 to 80° C., wherein the mass ratio of metal nitrogen carbon to fiber polymer is 1:10 to 10:1, and the mass ratio of fiber polymer to solvent is 1:8 to 1:
50.
8. The method according to claim 2, characterized in that: In step (3), the electrospinning syringe is added with 1-800 mL of the spinning solution, the voltage of the electrospinning needle is 5-40 kV, the capacity of the syringe is 5-1000 ml, the injection rate is 0.1-10 ml / h, the collection speed is 200-1000 rpm, the round-trip distance is 60.0-180.0 mm, the receiving distance is 5.0-40.0 cm, the spinning temperature is 10-50 ° C, the relative humidity is 10-60 RH%, the drying conditions are vacuum drying or blast drying, the drying temperature is 40-100 ° C, and the drying time is 2-48 h.
9. The method according to claim 2, characterized in that: In step (2) and step (4), the inert gas is one of Ar, He, and N2; in step (4), the secondary carbonization temperature is 500-1400°C, the time is 1-12h, and the heating rate of the secondary carbonization is 2-15°C / min; the gas flow rate of the inert gas is 10-150ml / min.
10. An application of the composite carbon nanofiber catalyst according to claim 1, characterized in that: The catalyst is used as an oxygen electrode in a fuel cell with oxygen participating in the reaction.
Citation Information
Patent Citations
Composite carbon fiber-loaded metal catalyst as well as preparation method and application thereof
CN103915633A
Bead-like cobalt-nitrogen co-doped carbon nanocage / carbon nanofiber composite catalyst and preparation method thereof
CN114420958A
Preparation method and application of zeolite-like imidazate skeleton / graphene catalyst
CN114976069A
Preparation method, product and application of porous bimetal-based ZnFe-N-C-atrGO composite electrocatalyst
CN116914167A
Soldering inspection equipment and soldering inspection method using the same
KR102150281B1
Cited By
In-situ growth MOG carbon nanofiber catalyst as well as preparation method and application thereof
CN120978096A
In-situ growth of mog carbon nanofiber catalyst, preparation method and application thereof
CN120978096B
Oxygen reduction catalyst for in-situ growth of two-dimensional MOF on electrostatic spinning surface and preparation method of oxygen reduction catalyst
CN121215781A